'Utterly Disgraceful': Social Media and the Workplace. Issue 3 (23rd March 2018) - Barnes, Alison; Balnave, Nikola; Holland, Peter
Abstract: Social media use by Australian public servants has given rise to questions pertaining to their political rights, impartiality and privacy outside of work. Drawing on the recent case Starr v Department of Human Services these issues are explored. The findings suggest that social media use has heightened tensions around public servant's rights to comment on issues of the day, and its use by employees both inside and beyond the workplace remains contested terrain. Abstract : Social media has become one of the most powerful communication tools inside and outside the workplace. The case study at the centre of this research paper highlights the tensions of this 21st century form of communication in the context of the public service, where social media use and its reach into the broader community have reignited debates around the impartiality of public servants and their political rights.